Taphonomic evidence supports an aquatic lifestyle for Spinosaurus. (January 2021) - Beevor, Thomas; Quigley, Aaron; Smith, Roy E.; Smyth, Robert S.H.; Ibrahim, Nizar; Zouhri, Samir; Martill, David M.
Abstract: A new locality near Tarda on the northern margin of the Tafilalt, south eastern Morocco exposes extensive sequences of the Ifezouane and Aoufous formations of the fluvial Kem Kem Group (Cretaceous, ?Albian-Cenomanian) on the south western flank of Ikfh n'Oufza escarpment of the Hamada du Meski. The stratigraphic sequence here differs significantly from better known exposures of the Kem Kem Group in the southern Tafilalt, and includes a heterolithic sequence of alternating grey mudstones and fine sandstones and a thin (~1.5 m) marine limestone. The locality is noteworthy for three vertebrate-bearing horizons within the upper part of the Ifezouane Formation. The upper two (Sites 1 and 2 in ascending order) are dominated by dental remains of the sawfish Onchopristis and the semi-aquatic theropod dinosaur Spinosaurus . Significantly, the remains of terrestrial dinosaurs constitute less than 1% of the total dental assemblage at Site 1 and 5.6% at Site 2. At Site 2 teeth of Spinosaurus outnumber the rostral "teeth" of Onchopristis . The remarkably high abundance of spinosaur teeth compared to remains of terrestrial dinosaurs, and even some aquatic animals strongly supports Spinosaurus being a largely aquatic animal spending much of its life in water where its teeth were shed and preserved.